Pengaruh Budaya Makan terhadap Indeks Massa Tubuh (IMT) pada Remaja - Syamsopyan Ishak; Suherman Rate; Afiska Prima Dewi; Ritma Dewanti; Hernianti Herman (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of the era and technological advances can make it easier for humans to do everything, one example is the development of types of food in Indonesia which is growing rapidly, one of which is junk food or fast food. The purpose of this study was to determine the effect of eating culture on Body Mass Index in adolescents. The type of research used is quantitative descriptive with a Cross Sectional Study approach, namely to determine the effect of dependent and independent variables observed in the same time period. This study was conducted in the Al-Fatah Natar Islamic Boarding School Area, South Lampung Regency, Lampung Province with a population of 30 students and a sampling technique of total sampling. The results of the statistical analysis of multiple logistic regression tests with results on the frequency of eating variables with a value of p (0.816)>α (0.05). While on the junk food consumption variable with a value of p (0.016)<α (0.05). The results of the statistical analysis show that only junk food consumption has an effect on Body Mass Index in adolescents. So it can be concluded that the culture of consuming junk food has an effect on Body Mass Index in adolescents. For the community to be able to more actively utilize the service facilities that have been prepared, so that through consultation with health workers can increase knowledge about good eating culture in adolescents.